a = ( 2+ √3 ) la a 2-a - √2 ( √5+ √3 ) - 2√3 ( 2 - √2 ) + √2 ( √5 - √3 ) , aratati ca a E ℕ .
REPEDE VA ROGGGGGGG
Răspunsuri la întrebare
Răspuns de
1
A = ( 2+ √3 )² - √2 ( √5+ √3 ) - 2√3 ( 2 - √2 ) + √2 ( √5 - √3 ) =
= (4+ 4√3+3 ) - (√10+ √6 ) - (4√3 - 2√6 ) + ( √10 - √6 ) =
=7+ 4√3 - √10 - √6 - 4√3 + 2√6 + √10 - √6 =
=7 7∈ N
= (4+ 4√3+3 ) - (√10+ √6 ) - (4√3 - 2√6 ) + ( √10 - √6 ) =
=7+ 4√3 - √10 - √6 - 4√3 + 2√6 + √10 - √6 =
=7 7∈ N
Theo16:
Multumesc ! :D
Răspuns de
0
Alte întrebări interesante
Informatică,
9 ani în urmă
Istorie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă